2016
DOI: 10.1186/s10194-016-0603-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression and anxiety on burden and management of episodic and chronic headaches – a cross-sectional multicentre study in eight Austrian headache centres

Abstract: BackgroundRecurrent and especially chronic headaches are associated with psychiatric comorbidities such as depression and anxiety. Only few studies examined the impact of depression and anxiety on episodic (EH) and chronic headache (CH), and data for Austria are missing at all. Therefore, the aim of the present study was to assess the impact of depression and anxiety on burden and management of EH and CH in patients from eight Austrian headache centres.MethodsWe included 392 patients (84.1 % female, mean age 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 36 publications
3
60
2
1
Order By: Relevance
“…Furthermore, an association of anxiety and depression with an elevated headache severity may be at least partially explained by an emotional and psychological component of pain perception [31]. In a previous multicentre clinical study, patients with headache and anxiety or depression had a significantly diminished quality of life and increased burden such as an unstable employment status, reduced earnings, and less success in their career [11]. Our population-based study is consistent with this prior study [11] and provides additional information about the association between anxiety and/or depression with diminished quality of life among patients with TTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an association of anxiety and depression with an elevated headache severity may be at least partially explained by an emotional and psychological component of pain perception [31]. In a previous multicentre clinical study, patients with headache and anxiety or depression had a significantly diminished quality of life and increased burden such as an unstable employment status, reduced earnings, and less success in their career [11]. Our population-based study is consistent with this prior study [11] and provides additional information about the association between anxiety and/or depression with diminished quality of life among patients with TTH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies reported that there is no significant difference between patients with TTH and patients with migraine (frequently associated with anxiety or depression) [6, 7] regarding psychiatric comorbidity [810]. In addition, anxiety and depression significantly affect sufferers’ quality of life and added a significant disability in patients with TTH [11]. …”
Section: Introductionmentioning
confidence: 99%
“…To explain this finding, it can be said that people that doubt their pain management abilities have a pessimistic evaluation of themselves due to these doubts and lose their ability to control pain and experience increased levels of anxiety. The onset of headache can adversely affect academic and job performances (Behrouz et al, 2013;Kurt & Kaplan, 2008;Zebenholzer et al, 2016); therefore, patients with poor pain self-efficacy may also experience anxiety due to their poor performances and the social consequences of failing at their job and academic duties and their accountability for them.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and especially anxiety have a greater chance of comorbidity with migraine headache, and these two symptoms significantly contribute to the overuse of medications for relieving headache. Researchers conclude that better outcomes can be accomplished in patients with headache through screening anxiety and depression and controlling them Mirzaei et al, 2016;Zebenholzer et al, 2016). Since depression and anxiety have a dramatic effect on the quality of life of patients with headache and increase the cost of care, multidimensional approaches to treat headache is mandatory for decreasing personal, occupational, and social disabilities in patients with headache (Zebenholzer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A final warning on the use of the Hospital Anxiety and Depression Scale (HADS) to assess psychiatric comorbidity [2, 3], because we risk misapplication and misinterpretation of findings. The HADS is a useful screening test for detecting symptoms of anxiety and depression one week before a probable hospitalization.…”
mentioning
confidence: 99%